2017
DOI: 10.7150/jca.17536
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-to-Alkaline Phosphatase Ratio: A Novel Prognostic Index of Overall Survival in Cisplatin-based Chemotherapy-treated Patients with Metastatic Nasopharyngeal Carcinoma

Abstract: The Albumin-to-Alkaline Phosphatase Ratio (AAPR) has been recently revealed as a prognostic index for hepatocellular carcinoma, whereas its role in metastatic nasopharyngeal cancer (NPC) remains unclear. The aim of this study was to evaluate the clinical value of AAPR in patients with metastatic NPC. We retrospectively reviewed 209 metastatic NPC patients treated with cisplatin-based regimens. Survival data were calculated using the Kaplan-Meier method and were compared using the log-rank test. Univariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 29 publications
2
57
0
Order By: Relevance
“…first reported the prognostic value of the AAPR and revealed that the AAPR was a significant prognostic predictor in hepatocellular carcinoma (HCC) . Similar studies have been subsequently reported in other types of cancers, including small cell lung cancer (SCLC) . However, the prognostic value of the AAPR has not yet been well studied in non‐small cell lung cancer (NSCLC) patients.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…first reported the prognostic value of the AAPR and revealed that the AAPR was a significant prognostic predictor in hepatocellular carcinoma (HCC) . Similar studies have been subsequently reported in other types of cancers, including small cell lung cancer (SCLC) . However, the prognostic value of the AAPR has not yet been well studied in non‐small cell lung cancer (NSCLC) patients.…”
Section: Introductionmentioning
confidence: 74%
“…the AAPR was found to be an independent prognostic factor for OS and DFS in patients with HCC regardless of the treatment approach . Since then, the AAPR has been proven to be a significant prognostic predictor for nasopharyngeal carcinoma, SCLC, and upper tract urothelial carcinoma (UTUC), whereas it has not yet been explored in patients with NSCLC …”
Section: Discussionmentioning
confidence: 99%
“…Full texts of these 16 remaining studies were assessed according to the inclusion and exclusion criteria, and 6 articles failed to offer sufficient prognostic information. Finally, as shown in Figure , a total of 10 studies comprising 7339 cases were included in this meta‐analysis . Patients were from different cancer centres and were assessed at different time points and differed in metastatic or non‐metastatic NPC.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, as shown in Figure 1, a total of 10 studies comprising 7339 cases were included in this meta-analysis. 20,21,[25][26][27][28][29][30][31][32] Patients were from different cancer centres and were assessed at different time points and differed in metastatic or non-metastatic NPC.…”
Section: Search Resultsmentioning
confidence: 99%
“…11 Subsequently, it has been reported as a novel prognostic factor in different malignant carcinomas, including nasopharyngeal carcinoma, pancreatic ductal adenocarcinoma, breast cancer, lung cancer, and cholangiocarcinoma. [12][13][14][15][16][17] However, the pretreatment level of AAPR and their prognostic role in cervical cancer have not ever been evaluated. Hence, we retrospectively studied the prognostic significance of AAPR in cervical cancer patients with stage IB-IIA disease, followed by the correlation of AAPR with other clinicopathological features.…”
Section: Introductionmentioning
confidence: 99%